EFFECTS OF GOAT FECES COMPOST RESIDUE AND SHALLOT ZPT ON THE GROWTH OF SHALLOT (Allium Fistulosum L.) - Gumelar, Asep Ikhsan; Ceunfin, Syprianus; Tae, Anggelinus (Universitas Veteran Bangun Nusantara, 2025)
This study aims to determine the effect of goat feces compost residue and plant growth regulators (PGR) on the growth and yield of spring onions (Allium fistulosum L.) in dry land. The study was conducted in February-April 2023 at the Dry Land Study Center, Timor University and the Laboratory of the Faculty of Agriculture, Timor University, North Central Timor Regency, East Nusa Tenggara. The study used a factorial randomized block design with two factors: first, residues of various doses of goat feces compost (control, 20 tons/ha, 30 tons/ha, 40 tons/ha), and second, shallot PGR with three concentrations (100 ml/L, 200 ml/L, 300 ml/L). The parameters observed included environmental conditions, growth, and plant yield. The results showed an interaction between goat feces compost residue and PGR on the number of leaves two weeks after planting and plant weight per plot. The application of goat feces compost fertilizer with a higher dose (20-40 tons/ha) increased plant growth, including the number of leaves, root length, root volume, and harvest index. Meanwhile, the application of shallot PGR significantly affected the harvest index, although it did not significantly affect other parameters. The right dose and concentration of both treatments can increase the yield of spring onions. This study shows that the right combination of goat feces compost fertilizer and PGR can increase plant yields, especially in dry land conditions.